Seasonal Variations of Major Anions in Water at Baro Haor of Kishoreganj, Bangladesh and Revealing The Suitability for Aquatic Resource Management (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2020)
Haors are areas with sweet water that inhabits a large variety of fishes and other aquatic animals. The quality of water in haors affects the lives in haors and the deterioration of the quality of water due to different anthropogenic reasons may affect the total ecosystem of haors. The study was conducted to investigate the physicochemical parameters and major anions of water of Baro haor area in Kishoreganj during the period from September 2016 to August 2017. The water samples were collected monthly during the pre-monsoon (Feb. to May), monsoon (Jun. to Sep.) and post-monsoon (Oct. to Jan.) seasons from five sampling stations as: (i) Bayershuil beel (St-1), (ii) Tegulia beel (St-2), (iii) Singpur beel (St-3), (iv) Neora beel (St-4) and (v) Bara beel (St-5). The physicochemical water quality was analyzed in the laboratory of the Department of Environmental Science and Resource Management (ESRM), Mawlana Bhashani Science and Technology University (MBSTU), whereas, anions were analyzed in Bangladesh Institute of Nuclear Agriculture (BINA), Mymensingh. Results of the study showed that the mean temperature, electrical conductivity (EC), total dissolved solid (TDS), dissolved oxygen (DO), biochemical oxygen demand (BOD), pH, alkalinity and hardness were found 28.03°C, 696.70 µS/cm, 484.35 mg/L, 6.62 mg/L, 2.36 mg/L, 7.40, 291.35 mg/L and 106.85 mg/L, respectively which revealed that the water was suitable for aquatic environment as well as fish production. Mean concentration of fluoride (F-), chloride (Cl-), bromide (Br-), nitrite (NO2-), nitrate (NO3-) and sulfate (SO42-) were 0.35, 121.35, 0.15, 5.63, 28.41 and 66.29 mg/L, respectively. The water quality was found suitable for aquatic environment and for fish production but the haor area is highly subjected to anthropogenic disturbances. To conserve the aquatic environment of the Baro haor regular monitoring and management should be taken to maintain the water quality.
Keywords: Water quality; anionic properties; seasonal variation; haor region